The force-time profile of elite front crawl swimmers - Formosa, D. P.; Mason, B.; Burkett, B. (Journal of Sports Sciences, 2011)
In this study, we used recently developed technology to determine the force-time profile of elite swimmers, which enabled coaches to make informed decisions on technique modifications. Eight elite male swimmers with a FINA (Federation Internationale de Natation) rank of 900+ completed five passive (streamline tow) and five net force (arms and leg swimming) trials. Three 50-Hz cameras were used to video each trial and were synchronized to the kinetic data output from a force-platform, upon which a motorized towing device was mounted. Passive and net force trials were completed at the participant's maximal front crawl swimming velocity. For the constant tow velocity, the net force profile was presented as a force-time graph, and the limitation of a constant velocity assumption was acknowledged. This allowed minimum and maximum net forces and arm symmetry to be identified. At a mean velocity of 1.92 ± 0.06 m/s, the mean passive drag for the swimmers was 80.3 ± 4.0 N, and the mean net force was 262.4 ± 33.4 N. The mean location in the stroke cycle for minimum and maximum net force production was at 45% (insweep phase) and 75% (upsweep phase) of the stroke, respectively. This force-time profile also identified any stroke asymmetry.